Comparative study of III-phosphide- and III-nitride-based light-emitting diodes: understanding the factors limiting efficiency. (29th September 2021) - Han, Dong-Pyo; Lee, Gyeong Won
Abstract: Modern light-emitting diodes (LEDs) require further improvements in the wall-plug efficiency (WPE). Thus, understanding and elucidating the physical factors limiting the WPE is of crucial importance. This study aims to understand and elucidate such factors via a comparative study of two different LED material systems, i.e. III-phosphide (AlGaInP) red and III-nitride (AlGaInN) blue LEDs. The WPE was decoupled into its component elements, which indicated that the dominant contribution to WPE reduction depends on the sample. To further investigate, thermodynamic and current component analyses were conducted. These analyses clearly demonstrated that the carrier dynamics is dependent of the material systems, i.e. internal quantum efficiency and voltage efficiency are simultaneously degraded due to the carrier accumulation in the blue sample. We found that the WPE can be improved using strategies dependent on the samples, such as improvement of the light extraction in the red sample and suppression of the carrier accumulation in the blue sample.